Preparation of Papers for IFAC Conferences & Symposia: Guidance, Navigation, and Control for Future Miniature Satellite Formations: Current Limitations and Impending Advancements. Issue 17 (2016) - Bangert, Philip; Busch, Stephan; Kramer, Alexander; Schilling, Klaus
Abstract: The usage of pico- and nano-satellites has seen a significant shift away from technology demonstration missions towards scientific and commercial projects in the field of Earth observation and communication networks. This contribution elaborates on the implications concerning the relevant Guidance, Navigation, and Control systems to meet the advanced requirements including recent developments made in the context of the NetSat pico-satellite formation mission.